(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes the first fantastic stories of the famous writer Tahir Malik. The writing of fantastic stories, the scope of the subject, the language are covered in detail. The story writing skills of the writer, the stories created in the pre-independence period are studied in this article.